PENGEMBANGAN MEDIA AUDIOVISUAL BERBASIS POWTOON PADA KETERAMPILAN MENULIS TEKS EKSPLANASI KELAS V SEKOLAH DASAR - Maharani, Nadya; Muhammadi; Yenti, Yesni; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop Powtoon-based audiovisual media for writing explanatory texts in fifth-grade elementary school that is valid, practical, and effective. This research used the Research and Development (R&D) method with the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The product was tested at SDN 01 Kapau and SDN 14 Gadut. Data were collected through validation sheets from material, media, and language experts, teacher and student response questionnaires, and tests to determine the effectiveness of the media. The results showed that the material expert validation obtained a percentage of 90% in the valid category, media expert validation obtained 86.25% in the valid category, and language expert validation obtained 92.5% in the valid category. The overall validation result was 89.5% in the valid category. The practicality test based on teacher responses obtained 95% at SDN 01 Kapau and 97.5% at SDN 14 Gadut, with an overall percentage of 96.25% categorized as very practical. Student responses obtained 92.75% at SDN 01 Kapau and 91.15% at SDN 14 Gadut, with an overall percentage of 91.95% categorized as very practical. The effectiveness test at SDN 01 Kapau increased from 74% in the pre-test to 92% in the post-test, with a final result of 83% categorized as effective. At SDN 14 Gadut, the results increased from 76.15% to 93.07%, with a final result of 84.61% categorized as effective. Therefore, the developed Powtoon-based audiovisual media is valid, very practical, and effective for Indonesian language learning in fifth-grade elementary school.